First-principles investigation of defects at GaAs/oxide interfaces. (February 2016) - Houssa, M.; Iordanidou, K.; Afanas'ev, V.V.; Stesmans, A.
Abstract: First-principles calculations of the ESR parameters of several point defects at GaAs/oxide interfaces and in bulk GaAsO4 are reported. Comparing the theoretical results with recent experimental data, obtained from ESR experiments on thermally oxidized GaAs surfaces, we first confirm the formation of As antisite defects at the GaAs/oxide interface during its thermal oxidation. Two other ESR active defects, which were not identified so far, are tentatively assigned to an As vacancy in the oxide and to a As dangling bond, backbonded to two O atoms and one As atoms, also present in the GaAs oxide layer. The formation of these oxide defects could be correlated to the As enrichment of the GaAs interface during its thermal oxidation.